The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s43247-022-00632-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of gasifying mixed plastic waste for hydrogen production and carbon capture and storage

Abstract: Waste plastic gasification for hydrogen production combined with carbon capture and storage is one technology option to address the plastic waste challenge. Here, we conducted a techno-economic analysis and life cycle assessment to assess this option. The minimum hydrogen selling price of a 2000 oven-dry metric ton/day mixed plastic waste plant with carbon capture and storage is US$2.26–2.94 kg−1 hydrogen, which can compete with fossil fuel hydrogen with carbon capture and storage (US$1.21–2.62 kg−1 hydrogen) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…The cost of post‐consumer HDPE was considered in the techno‐economic analysis. An estimated overhead cost of capital expenses and operating expenses was based on averages of work done by Lan and Yao for 2000 tons of plastic processed per day basis factory ($1.20 per kg H 2 ), [ 12 ] as well as work done by the National Renewable Energy Labs for 500 tons of biomass processed per day basis factory ($3.10 per kg H 2 ). [ 49 ] Overhead costs could be accurately modeled using software such as Aspen Plus, but this was deemed beyond the scope of this current work.…”
Section: Methodsmentioning
confidence: 99%
“…The cost of post‐consumer HDPE was considered in the techno‐economic analysis. An estimated overhead cost of capital expenses and operating expenses was based on averages of work done by Lan and Yao for 2000 tons of plastic processed per day basis factory ($1.20 per kg H 2 ), [ 12 ] as well as work done by the National Renewable Energy Labs for 500 tons of biomass processed per day basis factory ($3.10 per kg H 2 ). [ 49 ] Overhead costs could be accurately modeled using software such as Aspen Plus, but this was deemed beyond the scope of this current work.…”
Section: Methodsmentioning
confidence: 99%
“…26 On the economic side, Lan and Yao recently discussed that producing H 2 via wP gasification in the US could yield competitive costs with blue H 2 in the local market. 27 LCA has become the preferred approach for evaluating the environmental impact of technologies. 28 However, standard LCAs are mostly applied to compare alternatives as they lack thresholds beyond which a system should be deemed unsustainable, making the interpretation phase challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, Bhandari et al found that the electricity source heavily influences the environmental performance of electrolytic routes at the mid- and end point impact levels . On the economic side, Lan and Yao recently discussed that producing H 2 via wP gasification in the US could yield competitive costs with blue H 2 in the local market …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Consequently, there has been an unprecedented surge of multi-disciplinary research aimed at reducing plastic waste, limiting the production of virgin polymers, and improving pathways for PCPW to re-enter the value chain. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The development of automated optical sorting technologies for implementation at MRFs is one of these active research thrusts in the plastics recycling community. 28,29 This is because MRFs currently rely on air jets, magnetic separators, mechanical pistons, and human intervention to sort PCPW, all of which are methods that have been deemed insufficient to meet growing recycling demands.…”
Section: Introductionmentioning
confidence: 99%